Gender-specific reference values for high-sensitivity cardiac troponin T and I in well-phenotyped healthy individuals and validity of high-sensitivity assay designation - Giannitsis, Evangelos; Müller-Hennessen, Matthias; Zeller, Tanja; Schübler, Anna-Sophie; Aurich, Matthias; Biener, Moritz; Vafaie, Mehrshad; Stoyanov, Kiril M.; Ochs, Marco; Riffel, Johannes; Mereles, Derliz; Blankenberg, Stefan; et al. (Clinical biochemistry, 2020)
Objective - To determine gender-specific reference limits of high-sensitivity (hs) cardiac troponins (cTn) and validity of hs assay designation for both genders. - Methods - After screening with a questionnaire, 827 presumably healthy individuals were further selected based on clinical criteria (n = 740), clinical criteria plus cardiac imaging including stress magnetic resonance imaging or stress echocardiography (n = 726), and extended cardio-pulmonary parameters (n = 626). Blood samples were measured with hs-cTnT (Roche Diagnostics) on a cobas e602 analyzer as well as hs-cTnI (Abbott Diagnostics) on an ARCHITECTi2000SR. The impact of health definition, statistical methods, instrument selection and limit of detection (LoD) on overall and gender-specific 99th percentiles was assessed. - Results - Median age was 56 years (50.9% female) for the total study cohort. 99th percentiles for females and males ranged between 13.1 and 13.3 ng/L and 16.8-19.9 ng/L for hs-cTnT as well as 10.3-12.5 ng/L and 27.4-29.7 ng/L for hs-cTnI depending on health definition. Utilization of stricter health definition criteria reduced the difference of the gender-specific 99th percentiles between males and females for hs-cTnT to 3.7 ng/L (males 16.8 ng/L, females 13.1 ng/L), whereas the difference rather increased for hs-cTnI to 19.4 ng/L (males 29.7 ng/L, females 10.3 ng/L). Values > LoD could be measured in the majority of males and females using hs-TnT (81.4-83.3% and 96.5-96.9%, respectively). In contrast, values > LoD could not be observed in the majority of females using hs-cTnI (38.4-41.1%). - Conclusions - In a well-phenotyped healthy cohort, reference values for hs-cTnT were slightly higher, whereas hs-cTnI cut-offs were considerably lower than previously observed. Gender differences were more pronounced in hs-cTnI than in hs-cTnT and were further reduced for hs-cTnT by application of stricter health definition criteria. Contrary to hs-cTnI, hs-cTnT fulfilled criteria for hs designation for both genders.